When does hate hurt the most? Generational differences in the association between ethnic and racial harassment, ethnic attachment, and mental health. Issue 16 (10th December 2020) - Nandi, Alita; Luthra, Renee; Benzeval, Michaela
ABSTRACT: Using data from Understanding Society, this paper provides a comprehensive account of the associations between ethnic and racial harassment (ERH), mental health and ethnic attachment for ethnic minorities living in England. We find an association between ERH and poor mental health measured using GHQ for ethnic minorities, even after controlling for a rich array of individual and area level characteristics. We find that ethnic attachment, measured as ethnic identity and co-ethnic friendship ties, moderates this association but solely for UK born ethnic minorities. In contrast to previous research, we further find that living in areas of high co-ethnic concentration appears to exacerbate the association between ERH and mental ill-health.